Cardiac Concomitants of Feedback and Prediction Error Processing in Reinforcement Learning - Kastner, Lucas; Kube, Jana; Villringer, Arno; Neumann, Jane (Frontiers in Neuroscience, 2017)
Successful learning hinges on the evaluation of positive and negative feedback. We assessed differential learning from reward and punishment in a monetary reinforcement learning paradigm, together with cardiac concomitants of positive and negative feedback processing. On the behavioral level, learning from reward resulted in more advantageous behavior than learning from punishment, suggesting a differential impact of reward and punishment on successful feedback-based learning. Considering participants’ gender and weight status revealed less consistent behavioral adaptation in women compared to men, and obesity-related deficits in learning to avoid negative consequences. Importantly, learning and feedback processing were closely mirrored by phasic cardiac responses on a trial-by-trial basis: Negative feedback was accompanied by faster and prolonged heart rate deceleration compared to positive feedback. Moreover, cardiac responses shifted from feedback presentation at the beginning of learning to stimulus presentation later on. Most importantly, the strength of phasic cardiac responses to the presentation of feedback correlated with the strength of prediction error signals that alert the learner to the necessity for behavioral adaptation. These results provide strong new evidence for the notion that during learning phasic cardiac responses reflect an internal value and feedback monitoring system that is sensitive to the violation of performance-based expectations.